A new species of Picicola Clay and Meinertzhagen, 1938 (Phthiraptera: Ischno-cera) parasitic on the Rufous-sided Broadbill (Passeriformes: Eurylaimidae) in Ghana - Meyer, Mathys J.; Price, Roger D.; Johnson, Kevin P. (Zootaxa, 2008)
Picicola donwebbi, a new species of chewing louse from the Rufous-sided Broadbill (Smithornis rufolateralis Gray, 1864) collected in Ghana, is herewith described and illustrated. This is the first species of Ischnocera recorded from the broadbills (Passeriformes: Eurylaimidae) and, based on morphology, is placed in the Picicola quadripustulosus species group recorded from the Pittidae (Passeriformes). To evaluate its genetic distinctiveness and phylogenetic position in the Degeeriella complex, sequences of nuclear (elongation factor-1α) and mitochondrial (cytochrome oxidase I) genes for Picicola donwebbi are compared to various other species. Although this new species is genetically distinct, its phylogenetic position within the larger complex is unclear.